Gene cloning of an important eukaryotic translation initiation factor family, eIF2A gene in halophytic Leymus chinensis (Trin.) - Jin, Cheng-Wu; Sun, Yan-Lin; Hong, Soon-Kwan (Biotechnology, biotechnological equipment, 2014)
Eukaryotic initiation factors eIF2A and eIF2 both play important roles in the mRNA translation of protein synthesis, whereas the functions of eIF2A are usually overlooked, as both functions of binding methyionly-tRNA i (Met-tRNA i ) to 40S are similar under the same complementary factor and nucleotide requirements. Recently, the functions of eIF2A were reported to differ from those of eIF2 in manners when binding Met-tRNA i to 40S. Given that eukaryotic initiation factor eIF2 has been well known, eIF2A was still deficient in understanding of its sequence, structure and functions. In this work, we collected a high salt-tolerant grass Leymus chinensis (Trin.) as the object of study, and cloned and sequenced the eIF2A gene from this species. Based on the DNA alignment and analysis of eIF2A gene sequences from other organisms, an effective primer set was newly designed. Using this primer set, a DNA fragment with length of about 500 bp was obtained, and we have submitted this sequencing result to NCBI GenBank database (accession number: KF279515). The Basic Local Alignment Search Tool (BLAST) result showed that our sequence is highly identical to eIF2A gene sequences that existed in NCBI GenBank database. This work would help to further understand the function of eIF2A, and provide more potential target genes for studying their functions in relation to stress tolerance mechanisms.